2015
DOI: 10.1016/j.bbi.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hospitalization with infection during pregnancy and risk of autism spectrum disorders

Abstract: Animal models indicate that maternal infection during pregnancy can result in behavioral abnormalities and neuropathologies in offspring. We examined the association between maternal inpatient diagnosis with infection during pregnancy and risk of ASD in a Swedish nationwide register-based birth cohort born 1984-2007 with follow-up through 2011. In total, the sample consisted of 2,371,403 persons with 24,414 ASD cases. Infection during pregnancy was defined from ICD codes. In the sample, 903 mothers of ASD case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
227
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 291 publications
(244 citation statements)
references
References 36 publications
15
227
1
1
Order By: Relevance
“…A more expansive study by Zerbo et al (2015) found that maternal infection diagnosed at a hospital admission, especially bacterial ones, correlated with increased risk of ASD. A yet-larger 2015 study of over 24 000 Swedish ASD cases observed increased ASD rates among offspring of mothers hospitalized the year before pregnancy; risk for ASD increased under any inpatient diagnosis, including both viral and bacterial (Lee et al, 2015). The authors found no connection with the gestational timing of infection, however, in contrast to previous suggestions of viral or bacterial infection (Atladottir et al, 2010).…”
Section: Congenital Infectioncontrasting
confidence: 55%
“…A more expansive study by Zerbo et al (2015) found that maternal infection diagnosed at a hospital admission, especially bacterial ones, correlated with increased risk of ASD. A yet-larger 2015 study of over 24 000 Swedish ASD cases observed increased ASD rates among offspring of mothers hospitalized the year before pregnancy; risk for ASD increased under any inpatient diagnosis, including both viral and bacterial (Lee et al, 2015). The authors found no connection with the gestational timing of infection, however, in contrast to previous suggestions of viral or bacterial infection (Atladottir et al, 2010).…”
Section: Congenital Infectioncontrasting
confidence: 55%
“…2013; Lee et al. 2015). Exposure to anesthetics during a critical developmental time period is a major environmental insult to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the hypothesis tested, Fernell et al (2015) categorized data on ethnicity into three origin groups: Swedish, Miscellaneous (including nonScandinavian, South America, East Asia), and African/ Middle East. Other studies used a more specific term the maternal country of origin with various categorizations Idring et al 2014;Lee et al 2015;Zander et al 2015; see Table 4). …”
Section: Region Of Birth As Proxy For Ethnicity/culturementioning
confidence: 99%
“…Indeed, Bildt et al (2015) No Yes No (= not described) Domellöf et al (2014) No Yes No (= not described) Fernell et al (2015) Yes Yes The 1st cohort group: Bthe Stockholm Somali group^; the 2nd cohort group based in Gothenburg categorized as (a) Swedish, (b) miscellaneous (non-Scandinavian, South America, East Africa), (c) African/Middle East. Gardner et al (2015) Yes No Maternal country of birth categorized as (a) mother born in Sweden, (b) mother born outside Sweden Idring et al (2015) Yes No Maternal country of birth categorized as (a) mother born in Sweden, (b) mother born outside Sweden with low/high Human Development Index (HDI) Idring et al (2014) Yes Yes Maternal country of birth categorized as (a) mother born in Sweden, (b) mother born in Europe outside Sweden, (c) mother born outside Europe Lee et al (2015) Yes No Maternal country of birth categorized as (a) mother born in Sweden, (b) mother born in Europe outside Sweden, (c) mother born outside Europe Löfkvist et al (2014) Yes Yes Swedish language proficiency Lundström et al (2015b) Yes No No (= not described) McEvilly et al (2015) Yes No No (= not described) Selten et al (2015) Yes No Personal or parental history of migration Törn et al (2015) Yes No No (= not described) Zander et al (2015) Yes Yes Maternal country of origin a Coding based on the results reported by the first author/coder the Swedish Personal Data Act (PUL 1998) did not allow registering sensitive personal information such as race, ethnicity or other culture-related data such as religion. Therefore, the use of geographic area or country of origin as proxy for ethnicity by the researchers shown in this study justifies this approach.…”
Section: Scope Of Reporting Cultural Factorsmentioning
confidence: 99%